Concessivas num corpus da idade moderna - Costa, Ana Luísa (Associação Portuguesa de Línguística e Faculdade de Letras da Universidade do Porto, 2016)
Based on a corpus linguistics analysis, this study proposes a description of the syntactic distribution and semantic functioning of three concessive connectives in a Portuguese epistolary corpus from Early Modern Ages, the P.S. Post Scriptum. These connectives, embora, mesmo que and ainda que, are considered the most frequent conjunctions in Contemporary European Portuguese. Corpus analysis reveals a different diachronic path for each one. In the beginning of the 20th century, while embora frequency of use grows, it is evident the decrease of ainda que, with consequences in the concessive conjunctions system.
Keywords: Connectives; Conectores; Concessive conjunction; Conjunção concessiva; Grammaticalization; Gramaticalização; Corpus linguistics; Linguística de corpus